Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acsami.6b01767
|View full text |Cite
|
Sign up to set email alerts
|

Fast Fabrication of Sub-200-nm Nanogrooves Using Liquid Crystal Material

Abstract: Self-assembly of soft materials attracts keen interest for patterning applications owing to its ease and spontaneous behavior. We report the fabrication of nanogrooves using sublimation and recondensation of liquid crystal (LC) materials. First, well-aligned smectic LC structures are obtained on the micron-scale topographic patterns of the microchannel; then the sublimation and recondensation process directly produces nanogrooves having sub-200-nm scale. The entire process can be completed in less than 30 min.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Polymers having either LC molecular-philic or -phobic properties are put on a substrate by the spin-coating method. Frequently encountered polymeric materials are polyimide (PI) [33], polyethyleneimine (PEI) [34], and polyvinyl alcohol (PVA) [35]. Some reported methods for surface treatment involve self-assembled monolayers (SAMs) [36,37].…”
Section: Surface Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers having either LC molecular-philic or -phobic properties are put on a substrate by the spin-coating method. Frequently encountered polymeric materials are polyimide (PI) [33], polyethyleneimine (PEI) [34], and polyvinyl alcohol (PVA) [35]. Some reported methods for surface treatment involve self-assembled monolayers (SAMs) [36,37].…”
Section: Surface Treatmentmentioning
confidence: 99%
“…Since Choi et al [50] reported the exploitation of microchannels to generate periodic smectic defects, many experimental results using microchannels have been obtained [17,28,33,34,[51][52][53][54][55]. As LC materials should adopt a specifically defined orientation under limited volume and surface conditions of microchannels, the so-called confinement effect, they develop a peculiar structure in a periodic manner.…”
Section: Geometric Confinementmentioning
confidence: 99%
“…However, the rubbing process not only creates scrap, but also an electrostatic charge, which adversely affects the alignment of the liquid crystals. Accordingly, various alternative techniques for fabricating the crystal alignment layer have been proposed [1][2][3][4][5][6][7][8][9]. For example, Newsome et al [1] used a laser ablation technique to pattern grating structures on a polymer layer.…”
Section: Introductionmentioning
confidence: 99%
“…Gear et al [8] demonstrated that patterned nanogrooves using electron beam lithography can be used to control the magnitude of the azimuthal anchoring energy of liquid crystals. Kim et al [9] reported the fabrication of nanogrooves having sub-200-nm scale and the entire process can be completed in less than 30 minutes. In general, the results presented in [1][2][3][4][5][6][7][8][9] indicate that the molecular orientation of liquid crystals is significantly dependent on the shape of the grating pattern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation